Beirut Ammonium Nitrate Blast: Analysis, Review, and Recommendations - Al-Hajj, Samar; Dhaini, Hassan R.; Mondello, Stefania; Kaafarani, Haytham; Kobeissy, Firas; DePalma, Ralph G. (Frontiers in Public Health, 2021)
A massive chemical detonation occurred on August 4, 2020 in the Port of Beirut, Lebanon. An uncontrolled fire in an adjacent warehouse ignited approximately 2,750 tons of Ammonium Nitrate (AN), producing one of the most devastating blasts in recent history. The blast supersonic pressure and heat wave claimed the lives of 220 people and injured more than 6,500 instantaneously, with severe damage to the nearby dense residential and commercial areas. This review represents one of the first reports to provide an in-depth analysis of the Beirut blast and its health and environmental implications. It further reviews prior AN incidents and suggests actionable recommendations and strategies to optimize chemical safety measures, improve emergency preparedness, and mitigate the delayed clinical effects of blast and toxic gas exposures. These recommended actionable steps offer a starting point for government officials and policymakers to build frameworks, adopt regulations, and implement chemical safety protocols to ensure safe storage of hazardous materials as well as reorganizing healthcare system disaster preparedness to improve emergency preparedness in response to similar large-scale disasters and promote population safety. Future clinical efforts should involve detailed assessment of physical injuries sustained by blast victims, with systemic mitigation and possible treatment of late blast effects involving individuals, communities and the region at large.